Prorok strażnikiem życia. Próba odkrycia symboliki obrazów„Humanae vitae” 4, 18, 31 - Klimek, Piotr (Warszawskie Studia Teologiczne, 2019)
The article tries to find the symbolism of Pope Paul VI – the author of Humanae Vitae, pointing out that he can be attributed to the features found in the biblical image of the prophet protecting life. In the first part, various Old Testament words related to sentinel were analyzed, indicating that the most accurate is to use the root cph as a symbolic image of the pope as a watchman. Then consideration was given to life as a protected subject.